Energy Transition, De-Carbonization, and Capital Markets Nexus: Insights from BRICS Economies - Shakib, Mohammad; Ullah, Mirzat; Nawaz, Farrukh; Kayani, Umar; Sohag, Kazi; Mariev, Oleg (International Journal of Energy Economics and Policy, 2025)
This study investigates whether the capital markets of BRICS economies promote or hinder energy transition and de-carbonization within these regions. Using Driscoll-Kraay standard errors, we analyze the annual data from 2000 to 2021. We use Fixed Effects and Random Effects Generalized Least Squares (GLS) methods to validate our empirical results. The findings indicate that private sector credit deepening and stock market development exacerbate carbon dioxide emissions, undermining the potential for decarbonization in BRICS economies. Additionally, non-renewable energy intensity and GDP growth are found to contribute significantly to pollution emissions, further impeding decarbonization efforts within this economic bloc. The results reveal that FDI and energy transition play a crucial role in advancing de-carbonization in BRICS countries. This study proposes practical policy implications to mitigate emissions and support sustainable economic growth in the BRICS economies.